A federated framework for information systems development—sense making, argumentation or control of information systems development and its research - Kerola, Pentti (Accounting, management, and information technologies, 1996)
The main contribution of Hirschheim, Klein and Lyytinen's well-structured and significant paper is the idea of a federated framework for information systems development and its research, based on the social action theories of Habermas and Etzioni. This comment presents the most essential reasons for reformulating the Etzioni dimension (primary domains of changes in ISD) for its adoption into the framework: the matrix of object systems classes. The most essential changes concern the human actor as the ontological subject/object in ISD and its research, and the inclusion of actors in all the categories of differential malleability in the domains of change. Comment is also directed at the metatheoretic nature of their paper and its potential embedded misunderstandings. Awareness of other researchers' frames and their incongruences is especially emphasized in order to increase common sense making in the research community.